2011
DOI: 10.1152/ajpgi.00474.2010
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal myofibroblasts: targets for stem cell therapy

Abstract: The subepithelial intestinal myofibroblast is an important cell orchestrating many diverse functions in the intestine and is involved in growth and repair, tumorigenesis, inflammation, and fibrosis. The myofibroblast is but one of several α-smooth muscle actin-positive (α-SMA(+)) mesenchymal cells present within the intestinal lamina propria, including vascular pericytes, bone marrow-derived stem cells (mesenchymal stem cells or hematopoietic stem cells), muscularis mucosae, and the lymphatic pericytes (colon)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 130 publications
8
116
0
2
Order By: Relevance
“…As expected, NG2 staining identified pericytes closely associated with villus blood capillaries ( Figure 1C) and a dense network of cells between villus epithelial cells and blood capillaries, which are most likely subepithelial myofibroblasts (20). Although previous studies in tissue sections suggested the presence of vascular smooth muscle cells (SMCs) on lacteals and blood capillaries (21,22), we failed to confirm this observation in our 3D analysis ( Figure 1, D and E). Instead, in agreement with high villus contractility (23), we observed tree-like smooth muscle fibers (Figure 1, D-F), identified by α-smooth muscle actin (αSMA) and desmin staining (Supplemental Figure 1C).…”
Section: Introductionmentioning
confidence: 43%
See 1 more Smart Citation
“…As expected, NG2 staining identified pericytes closely associated with villus blood capillaries ( Figure 1C) and a dense network of cells between villus epithelial cells and blood capillaries, which are most likely subepithelial myofibroblasts (20). Although previous studies in tissue sections suggested the presence of vascular smooth muscle cells (SMCs) on lacteals and blood capillaries (21,22), we failed to confirm this observation in our 3D analysis ( Figure 1, D and E). Instead, in agreement with high villus contractility (23), we observed tree-like smooth muscle fibers (Figure 1, D-F), identified by α-smooth muscle actin (αSMA) and desmin staining (Supplemental Figure 1C).…”
Section: Introductionmentioning
confidence: 43%
“…We next measured lacteal length as a percentage of the blood capillary cage length and the number of filopodia/lacteal. Interestingly, relative lacteal length was constant in the different intestinal segments (60%-70% of villus length), and the number of lacteal blasts (21). The SMC network extends throughout the entire villus length and is focally in close proximity to lacteals (Figure 1, E and F), whereas the terminal ends of SMC fibers are closely associated with villus blood capillaries ( Figure 1G).…”
Section: Resultsmentioning
confidence: 96%
“…The conditions that support generation of organoids from IESCs were modified to include exogenously supplied recombinant WNT3a, as well as an underlying layer of MFs derived from embryonic murine intestine. Pericryptal MFs have been implicated in the support of epithelial growth and development by secreting mitogens and morphogens in the IESC zones (23,32). These new conditions supported development of mature colonoids, which formed from isolated whole crypts (Fig.…”
Section: Colonic Epithelial Cells Expressing the Highest Level Of Soxmentioning
confidence: 99%
“…The crypts of Lieberkuhn contain stem cells that give rise to proliferating daughter/progenitor cells, which differentiate into the four major cell types of the intestine. Surrounding stromal cells, including myofibroblasts, play a critical role in modulating epithelial cell proliferation (19,22) and carcinogenesis (34). Stromal myofibroblasts that encircle the intestinal crypts contribute to maintaining the normal stem cell niche (19,26,32,37), and tumor-associated myofibroblasts play a critical role in promoting epithelial carcinogenesis, in part by regulating cancer stem cells (27,31,34) and enhancing tumor growth (2,16).…”
mentioning
confidence: 99%